Dapagliflozin Promotes Neovascularization by Improving Paracrine Function of Skeletal Muscle Cells in Diabetic Hindlimb Ischemia Mice Through PHD2/HIF-1α Axis - Nugrahaningrum, Dyah Ari; Marcelina, Olivia; Liu, Caiping; Wu, Shourong; Kasim, Vivi (Frontiers in Pharmacology, 2020)
Diabetes mellitus is associated with high risk of hindlimb ischemia (HLI) progression and inevitably poor prognosis, including worse limb salvage and mortality. Skeletal muscle cells could secrete angiogenic factors, which could promote neovascularization and blood perfusion recovery. Thus, paracrine function of skeletal muscle cells, which is aberrant in diabetic condition, is crucial for therapeutic angiogenesis in diabetic HLI. Dapagliflozin is a well-known anti-hyperglycemia and anti-obesity drug; however, its roles in therapeutic angiogenesis is unknown. Herein, we found that dapagliflozin could act as an angiogenesis stimulator in diabetic HLI. We showed that dapagliflozin enhances the viability, proliferation and migration potentials of skeletal muscle cells; and promotes the secretion of multiple angiogenic factors from skeletal muscle cells, most plausibly through PHD2/HIF-1alpha axis. Furthermore, we demonstrated that conditioned medium from dapagliflozin-treated skeletal muscle cells enhances the proliferation and migration potentials of vascular endothelial and smooth muscle cells, which are two fundamental cells of functional mature vessels. Finally, in vivo study demonstrated that intramuscular administration of dapagliflozin effectively enhances the formation of mature blood vessels and subsequently, blood perfusion recovery in diabetic HLI mice. Hence, our results suggest a novel function of dapagliflozin as a potential therapeutic angiogenesis agent for diabetic HLI.